Potentiation by granulocyte macrophage colony-stimulating factor of lipopolysaccharide toxicity in mice. - Tiegs, G (1994)
GM-CSF is known to prime leukocytes for inflammatory stimuli in vitro. The objective of this study was to investigate the role of GM-CSF in vivo in a systemic inflammatory reaction syndrome. The results demonstrate a potentiation of LPS toxicity by GM-CSF in a mortality model as well as in a septic liver failure model in mice. Pretreatment of animals with 50 micrograms/kg GM-CSF induced lethality within 24 h in mice challenged with a subtoxic dose of LPS while controls survived > 72 h. A monoclonal anti-GM-CSF antibody significantly protected against a lethal LPS dose. Serum GM-CSF was inducible by LPS and peaked at 2 h. GM-CSF pretreatment dramatically potentiated systemic TNF release and hepatotoxicity induced by a subtoxic dose of LPS in galactosamine-sensitized mice. Potentiation of LPS hepatotoxicity was possible until 30 min after LPS challenge. Polyclonal anti-GM-CSF IgG protected against septic liver failure in this model and attenuated serum TNF concentrations. In vitro an ex vivo experiments revealed that after GM-CSF pretreatment LPS-induced IL-1 release from bone marrow or spleen cells was also enhanced. These findings suggest that GM-CSF represents an endogenous enhancer of LPS-induced organ injury, possibly by potentiating the release of proinflammatory cytokines such as TNF and IL-1.